Health literacy and associated factor among undergraduate students in Nepal. - Bhusal, Sandesh (2021)
SUMMARY: Health literacy is one of the most critical aspects of health promotion in public health. It is a challenge to healthcare provision all over the world. People sometimes have difficulties in seeking health care, understanding health information, adherence to medical regimen, etc. which have a potential role in self-care and management of chronic diseases The World Health Organization (WHO) has positioned health literacy as a key mechanism to meet the health-related Sustainable Development Goal (SDG3). However, there is little known about the status of health literacy in developing countries such as Nepal. Limited health literacy is concerned with adverse health outcomes and a huge financial burden on society. However, the gap exists in the knowledge of health literacy, especially among undergraduates. Universities are important settings for health promotion. Undergraduate is the stage with the greatest learning potential and the stage is critical for forming the framework of health literacy. For many students, the university is a period of transition from teenager to young adult, moving out of home and relying less on parents to make health-related decisions. In Nepal, there are currently no studies evaluating the health literacy levels among university students in terms of health and non-health student groups. Hence, this study was conducted to assess the level of comprehensive health literacy and factors determining limited health literacy among undergraduate students of Tribhuvan University Nepal. A web-based cross-sectional survey was conducted to recruit 466 undergraduate students proportionately from five institutes of Tribhuvan University, Nepal. The 16-item short version of the European Consortium for Health Literacy Questionnaire was used to measure students' health literacy levels. IBM SPSS version 20 was used to analyze the data. The study found than 61.2% of students have limited health literacy (24.7% had "inadequate" and 36.5% had "problematic" health literacy). Age, student's sector, self-rated financial status were found to be significantly associated with limited health literacy. Teenagers are 2.13 times more likely to have limited health literacy compared to students of age group more than 20 years (OR= 2.13, 95% CI: 1.22- 3.70). Health literacy was lower among students from non-health sector compared to health sector. Students belonging to non-health-related majors had higher odds of having limited health literacy compared to students who belonged to the health related majors (OR= 1.9, 95% CI: 1.25- 2.9). Similarly, Students who reported having poor financial status were 2.39 times more likely to have limited health literacy compared to students who reported having good financial status (OR= 2.39, 95% CI: 1.15 - 4.96). When analyzing the participant's performance based on four health literacy dimensions students scored high on dimension dealing with understanding health information while they scored low on dimension dealing with appraising health information. More than three-fifths of the undergraduates were found to have limited health literacy. This study indicates university students should not be assumed to be health-literate and interventions to improve students' health literacy. Integration of health related curricula especially for those whose majors are not health related would be better.